2015
DOI: 10.1364/oe.23.029449
|View full text |Cite
|
Sign up to set email alerts
|

Vertical silicon waveguide coupler bent by ion implantation

Abstract: We propose and demonstrate that vertically curved waveguides (VCWs) enable vertical coupling between silicon wire waveguides and optical fibers with low wavelength dependence and polarization dependence for wide telecommunication wavelength band light. To bend these VCWs, we implanted silicon ions into silicon wire cantilevers from the vertical direction. The internal stress distribution that was induced by ion implantation drove the bending force, and we achieved vertical bending of the waveguides, with curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In addition, the sputtering effect will be enhanced in low‐lying areas, and then, the surface of materials will become rougher . Some researchers have reported that ion irradiation can modulate the surface roughness and bending direction of nanowires (NWs) . For example, Yoshida et al reported that silicon wire cantilevers can be bent by Si ion irradiation .…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the sputtering effect will be enhanced in low‐lying areas, and then, the surface of materials will become rougher . Some researchers have reported that ion irradiation can modulate the surface roughness and bending direction of nanowires (NWs) . For example, Yoshida et al reported that silicon wire cantilevers can be bent by Si ion irradiation .…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
“…Some researchers have reported that ion irradiation can modulate the surface roughness and bending direction of nanowires (NWs) . For example, Yoshida et al reported that silicon wire cantilevers can be bent by Si ion irradiation . Figure shows the scanning electron microscopy (SEM) images of the vertical curved waveguide.…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
See 1 more Smart Citation
“…This case is referred to as surface coupling. Surface-coupled PIC may, e.g., rely on grating couplers, SiP waveguides that are bent upwards by ion implantation [31], or on 3D-printed lensed couplers [32]. We only give a summary of the results here; mathematical details can be found in Appendix B.…”
Section: Theoretical Analysis Of Non-planar Switch-and-select (Sas) Cmentioning
confidence: 99%
“…[27]- [29] As IIB can be induced using either dopant or inert-gas ion beams, the bending can therefore occur in the processing of nanostructured semiconductors during both the pre-amorphisation step and the subsequent doping . [20], [25] As well as showing potential for future transistor technologies, IIB has also been used by Yoshida et al [30] to create waveguides by bending silicon wires using self-ion irradiation. [30] Furthermore, as straining of germanium nanowires is being investigated as a way of optically activating germanium, IIB might modify the optoelectronics properties of germanium as residual strain is expected to be present in bent nanowires .…”
Section: Introductionmentioning
confidence: 99%